(untitled) (Revista Inclusiones, 2019)
Culture is a powerful human tool for survival, but it is a fragile phenomenon. It is constantly changing and easily lost because it exists only in our minds. Cultures are not the product of lone individuals. They are the continuously evolving products of people interacting with each other. Culture refers to the pattern of human activity and the symbols, which give significance to this extension endeavor. A community gains a character and a personality of its own, because of the culture of its people. Culture is shared by the members of a community. It is learned and passed from the older generations to the newer ones. For an effective transfer of culture from one generation to another, it has to be translated into symbols. Language, art and related practices. These things serve as symbolic means of transfer of cultural values between generations. Culture is a bond that ties the people of a region or community together. One of the significant culture among community folks in the town of Pililla was the existence of then “Sabutan weaving culture”. The culture served as an avenue to enable parents who are not employed elsewhere to earn significant amount to send their kids to school and buy nutritious foods for the family according to old community folks who have the memories of the past. Further, due to conversion of land use from being Sabutan plantation into residential area, the industry slowly died together with the shifting of community interest from native products to the use plastics. Sabutan fiber is primarily used for manufacturing hats. Headwear made of sabutan is strong and durable. Sleeping mats of excellent quality are made from sabutan fibers either in their natural color or dyed shades. Sabutan is also an excellent material for cushions and is good for making handbags, picture frames, and other fancy articles